On the Aploderus species of Turkey (Coleoptera: Staphylinidae, Oxytelinae) - Assing, Volker (Zootaxa, 2007)
Two microphthalmous species of Aploderus Stephens from Turkey are described, illustrated, and distinguished from their closest relative, A. schweigeri (Smetana): A. magniceps sp. n. and A. capitulatus sp. n. Their distributions are mapped. The first record of A. endogaeus Assing since its original description is reported; the previously unknown male sexual characters of this species are illustrated. A key to the Western Palaearctic species of the genus is provided.